2013
DOI: 10.1097/gme.0b013e3182611574
|View full text |Cite
|
Sign up to set email alerts
|

Role of antimüllerian hormone as a biomarker of the menopausal transition

Abstract: When AMH levels fall below detectable levels, women at the menopausal transition will progress to menopause within 3 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
0
7
0
2
Order By: Relevance
“…These data may be of help to women contemplating the option of oocyte cryopreservation or to couples and individuals who are considering when to begin to try to conceive. While longitudinal studies exist and are in process regarding the predictive ability of AMH by age to forecast the final menstrual period [1,10], what is of interest to women of reproductive age who are seeking to become pregnant at a later age is their likelihood of success of conception. Therefore, continued research on the potential impact of the FMR1 gene on ovarian reserve (which includes the diagnostic value of AMH measurements) and fertility is important for providers of fertility care and their patients.…”
Section: Discussionmentioning
confidence: 99%
“…These data may be of help to women contemplating the option of oocyte cryopreservation or to couples and individuals who are considering when to begin to try to conceive. While longitudinal studies exist and are in process regarding the predictive ability of AMH by age to forecast the final menstrual period [1,10], what is of interest to women of reproductive age who are seeking to become pregnant at a later age is their likelihood of success of conception. Therefore, continued research on the potential impact of the FMR1 gene on ovarian reserve (which includes the diagnostic value of AMH measurements) and fertility is important for providers of fertility care and their patients.…”
Section: Discussionmentioning
confidence: 99%
“…About 15% of the female population faces infertility issues because of premature ovarian failure [ 26 ]. Anti-Müllerian hormone has been proven to be a sensitive biomarker for detecting the menopausal transition [ 27 ]. Another study [ 28 ] suggested that low serum anti-Müllerian hormone levels are an indication of early ovarian aging.…”
Section: Biomarkers Of Common Reproductive Impairments In Femalesmentioning
confidence: 99%
“…Ethnicity also may influence serum AMH [39]. Interestingly, a recent study in 44 Japanese women demonstrated after AMH became undetectable, menopause onset was within 3 years [40], instead of 5 years shown by a study of large U.S. and European populations [41], although the study design and assay performance may contribute to these observational differences.…”
Section: Menopausementioning
confidence: 99%